Memory and political project in Plinio’s Panegyric - Alfaro, Juan Pablo (Romanitas - Revista de Estudos Grecolatinos, 2016)
The Principates of Nerva (96-99) and Trajan (99-117) represent a particular moment in Roman History in which the design of a “political project” for the imperial regime is recognized. Fabricated by a group of aristocratic intellectuals grouped around the figure of Pliny the Younger, this project was designed to resolve the inherent tension between the aristocracy and the emperor. From the analysis of the Panegyricus of Trajan, in the present work we will investigated the central aspects of these project, the rhetorical strategies to put it on and the function achieved, in this sense, by the memory of the recent past of the Principate, built there. A memory whose basic aspects are re-project in the historical works of Tacitus and Suetonius, members of the “intellectual circle” of Pliny and participants of his political project, and that legated us greatly the images of the Caesars of the first century that we have nowadays.